Co-Production and Managed Competition in Mixed Quasi-markets - Flavio Delbono; Diego Lanzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
In this paper, we provide a very simple model to shed light on the issue of managed competition in mixed quasi-markets (i.e. regulated markets in which social and for-proÖt Örms coexist). In doing this, we consider the literature on mixed oligopolies as a reasonable reference point and try to enrich it with the idea of quasi-market. Firstly, our results show that social Örms serve the relatively richer portion of the population. Only relatively poor consumers buy units of service from the proÖt-oriented Örm. Secondly, the socially-preferable form of managed competition is to introduce coproduction practices and, hence, to raise proÖt-oriented Örmís production costs. The diffusion of coproduction paradigms ensures maximal service quality and eliminates mark-up from the market.
Keywords: I18; L13; L84; 330